Validation and diagnostic study of cloudburst events over the Himalayan region using IMDAA and ERA5 - Nitin Lohan; Ashish Routray; Rohan Kumar; Biranchi Kumar Mahala; Sushil Kumar (Geomatics, Natural Hazards & Risk)
A cloudburst is characterised by intense localised rainfall over a brief period, often resulting in significant damage, particularly in high-elevation areas like the Himalayan region. Consequently, it is crucial to anticipate these disastrous events to avoid the associated damage. The objective is to compare the performance of two reanalysis datasets i.e. Indian Monsoon Data Assimilation and Analysis (IMDAA) and fifth-generation European Centre for Medium-Range Weather Forecasts (ERA5), to comprehend the atmospheric dynamics associated with the cloudburst events over the Himalayan region. Four cloudburst cases are analysed during the Southwest Monsoon season, affecting areas at elevations between 1600 and 2100 meters. Daily accumulated rainfall from both reanalyses is compared with the Global Precipitation Measurement (GPM). The results indicate that IMDAA outperforms ERA5, with a mean Pearson correlation of 0.56 versus 0.35, though both datasets underestimate rainfall. IMDAA shows a minor underestimation with a mean bias of −0.74 mm, while ERA5 underestimates more significantly, with a mean bias of −2.52 mm. Additionally, various atmospheric parameters, including vertically integrated moisture transport, relative humidity, wind fields, potential vorticity, outgoing longwave radiation, and various instability indices, are analysed to investigate the mechanisms behind these cloudburst events. Overall, the high-resolution IMDAA reanalysis outperformed the low-resolution ERA5.